The impact of COVID-19 on essential health service provision for endemic infectious diseases in the South-East Asia region: A systematic review - Laura E. Downey; Thomas Gadsden; Victor Del Rio Vilas; David Peiris; Stephen Jan (Elsevier, 2022)
Summary: Background: There is increasing evidence that the COVID-19 pandemic has impacted adversely on the provision of essential health services. The South East Asia region (SEAR) has experienced extremely high rates of COVID-19 infection, and continues to bear a significant proportion of communicable disease burden worldwide. Methods: We conducted a systematic literature review of quantitative evidence to estimate the impact of COVID-19 on the provision of essential prevention, detection, treatment, and management services for five high-burden infectious diseases across the SEAR. Findings: A total of 2338 studies were reviewed, and 12 studies were included in our analysis, covering six countries across the SEAR (Bhutan, Sri Lanka, Nepal, Myanmar, Thailand, and India) for three conditions of interest (HIV, TB, dengue fever). We identified significant disruption to TB testing (range=25% to 77.9%) and diagnoses (range=50% to 58%) in India, Nepal, and Indonesia; and similar disruptions were observed for screening, new diagnoses and commencing HIV treatment in India and Thailand. There was also drastically reduced case detection for dengue fever (range=75% to 90% disrupted) in Bhutan and Sri Lanka. No studies were identified for malaria nor hepatitis in any country, and nor for any service in the remaining six SEAR countries. Interpretation: We identified evidence of significant disruption to the prevention, diagnoses, treatment, and management of TB, HIV, and dengue fever due to the COVID-19 pandemic across multiple SEAR country settings. This has the potential to set back hard-fought gains in infectious disease control across the region. The lack of evidence for the impact of the pandemic on malaria and hepatitis services, and in the remaining six SEAR countries, is an important evidence gap that should be addressed in order to inform future policy for service protection and pandemic preparedness. Funding: This work was supported by the WHO Sri Lanka Country office.